Retinal and choroidal microvascular assessment of children receiving recombinant growth hormone therapy - Ismail Omar; Yousra Samir Fadle; Noura M. Ibrahim El Bakry (International Journal of Retina and Vitreous)
Abstract Background The purpose of this study is to evaluate the retinal and choroidal microvascular state in children with congenital isolated growth hormone deficiency (IGHD) and determine the effect of recombinant human growth hormone treatment on these structures compared with healthy controls. Methods The study included children with IGHD under recombinant human GH treatment as group one and another group of healthy controls. Both groups were examined using optical coherence tomography angiography (OCTA). Data concerning superficial capillary plexus (SCP), deep capillary plexus (DCP), choriocapillaris (CC), and retinal thickness were recorded. Results The study included two equal groups of 30 individuals. Both groups had no statistically significant differences in age, gender, weight, or spherical equivalent. However, subjects of group II were taller than those of group I (p = 0.011). OCTA images of the SCP, DCP, and CC vessel density revealed statistically non-significant differences between the two groups. Conclusion Children receiving recombinant growth hormone therapy showed no changes in the retinal and choroidal microvasculature or macular thickness. Trial registration number 1094/03/2024 by Minia University Faculty of Medicine Institutional Review Board. Another registration number is UMIN000055654.